MAKNA CANTIK DALAM IKLAN MAGNIFICENT MEANING IN ADVERTISING - Freddy Yusanto M.Ds (Lingkar Studi Komunikasi (LISKI), 2018)
Many theories explain the definition of beauty; it is said that it is seen from their outer beauty and inner beauty, however many Indonesian women still have a strong perception that beautiful women are the ones with bright skin, long hair and slim.Clean & Clear products try to see the meaning of beautiful from its different point of view. It should not be white, long-haired and slim, therefore Clean & Clear ads show female models with different perception of 'beautiful' women in general. This study aims to determine the meaning of outer beauty and inner beauty in Clean & Clear ads version of '1000 tribes Indonesia, different skin colors'. The method used in this research is qualitative research by using semiotics analysis Roland Barthes by focusing on the sign of denotation, connotation, and myth based on critical paradigm. Data collection techniques used here are Clean & Clear ads version of '1000 Indonesian tribe, different skin color as the primary data and reference book, paper and article as the secondary data. The result of study shows that Clean & Clear ads try to highlight inner beauty through high confidence, a loose smile showing the happiness of women who are seen different from their outer beauty, they do not have bright skin and long black hair. Otherwise in this ad, researchers see there is one component of beauty still maintained by Clean & Clear, that is about a slim body. It is seen from the nine female models featured in this ad, all of them are slim. As we all know that many women who are not slim, they are still obsessed to look beautiful. Keywords: Semiotics, Advertising & Clear, Inner beauty, Outer beauty